2012
DOI: 10.9734/bjpr/2012/1870
|View full text |Cite
|
Sign up to set email alerts
|

Potential Larvicidal Properties of Blighia sapida Leaf Extracts against Larvae of An. gambiae, Cu. quinquefasciatus and Ae. aegypti

Abstract: Blighia sapida is a medicinal plant used in Southern Nigeria for the treatment of some eye ailments and headache. The Centre for Scientific Research into Plant Medicine (CSRPM), Ghana, has used this plant for the treatment of diarrhea for over 20 years. Objective: This study was designed to investigate the lethal effect of aqueous, ethanol, and ethyl acetate extracts of the leaf of B. sapida on fourth instar larvae of An. gambiae, Cu. quinquefasciatus and Ae. aegypti. Methods: The lethal effect of aqueous, eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
3
10
0
1
Order By: Relevance
“…Earlier studies confirmed the insecticidal effects of these plants species: B. ferruginea [45]; B. sapida [15,36,[50][51][52][53]; and K. senegalensis [54][55][56][57][58][59]. Acetone extract of K. senegalensis showed the lowest LC 50 and the biggest toxicity ratio, consequently the most toxic on D. porcellus.…”
Section: Psychementioning
confidence: 72%
See 3 more Smart Citations
“…Earlier studies confirmed the insecticidal effects of these plants species: B. ferruginea [45]; B. sapida [15,36,[50][51][52][53]; and K. senegalensis [54][55][56][57][58][59]. Acetone extract of K. senegalensis showed the lowest LC 50 and the biggest toxicity ratio, consequently the most toxic on D. porcellus.…”
Section: Psychementioning
confidence: 72%
“…Insecticidal effect of the three botanicals may also be due to its active components. Insecticide activity of B. sapida is primarily due to saponins and tannins [36,44] and might be the cause of the insecticidal activity in this study. K. senegalensis leaf powder possesses limonoids which have a wide range of biological activities, including insecticidal, insect antifeedant, and growth regulating activity on insect [14].…”
Section: Psychementioning
confidence: 86%
See 2 more Smart Citations
“…Jika nilai LC semakin rendah maka insektisida botani tersebut akan semakin efektif, sehingga ekstrak etanol daun mahoni lebih efektif dari pada ekstrak air daun mahoni. Hasil penelitian ini serupa dengan hasil penelitian beberapa peneliti yang membandingkan efektivitas ekstrak etanol dan air dari berbagai tumbuhan untuk membunuh larva nyamuk, yakni Ubulom et al (2012) dan Nagappan (2012).…”
Section: Efektivitas Ekstrak Etanol Daununclassified